Foreign Firms: Powerful or Persecuted? - Emma Aisbett (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
International economists often refer to multinational enterprises and foreign firms interchangeably, yet one of the enduring divisions in the globalization debate is whether international law should be strengthened to protect foreign firms from predatory host governments, or rather strengthened to protect host governments from powerful multi- national firms. We contribute to this debate conceptually by distinguishing between foreign firms and multinational firms. We then use firm level data on government-firm relations from eighty countries to contribute empirical evidence on the debate. We find that multinational firms (both foreign and local) are indeed relatively influential over government, and find no evidence that foreign firms (multinational or otherwise) suffer significant disadvantages in terms of self-reported influence.
Keywords: 330; Multinational Firms; Foreign Firms; Political Economy; Government